The genus Clubiona Latreille, 1904 (Araneae: Clubionidae) in the Maghreb, with notes on the genevensis group and new records from the Mediterranean Region - Bosmans, Robert; Henrard, Arnaud; Benhalima, Souâd; Kherbouche-Abrous, Ourida (Zootaxa, 2017)
A survey of the members of the genus Clubiona Latreille, 1904 in the Maghreb is presented. The presence of Clubiona comta C. L. Koch, 1839, C. dinienis Simon, 1878, C. leucaspis Simon, 1932, C. phragmitis C. L. Koch 1843 and C. vegeta Simon, 1918 is confirmed. Clubiona pseudosimilis Mikhailov, 1990, from the eastern Mediterranean is new to Africa and Portugal. A specimen of C. neglecta O. Pickard-Cambridge, 1862, cited from Morocco in the past, was misidentified and appears to be C. pseudoneglecta Wunderlich, 1994. The species is new to Algeria and Spain. Two new synonyms are revealed: Clubiona baborensis Denis, 1937 from Algeria = C. diniensis Simon, 1878 N. Syn. and Clubiona venusta Pavesi, 1880 from Tunisia = Selamia reticulata (Simon, 1870) N. Syn. Clubiona mandibularis Lucas, 1846 is considered a Nomen dubium. The comta group is redefined and the “genevensis subgroup” is elevated to species group, including two subgroups. A key and illustrations to the species of the genevensis group are presented and all the species occurring in the Maghreb are illustrated.